Diagnostic ability of miR-19a and Let-7f along with platelet and leukocyte extracellular vesicles in acute ischemic stroke patients. (3rd October 2022) - Eyileten, C; Nowak, A; Shahzadi, A; Jarosz-Popek, J; Jakubik, D; Gasecka, A; Van Der Pol, E; Wolska, M; Mirowska-Guzel, M; Czlonkowska, A; Postula, M
Abstract: Background: Ischemic stroke (IS) is one of the most frequent causes of death. Since miRNAs have been illustrated to play an important role in various processes through regulation of multiple genes, and platelet function, their utility as novel biomarkers should be determined. Purpose: We aimed to analyze the circulating platelet-derived miR-19a-3p, miR-186-5p, Let-7f, platelet-extracellular vesicles (EVs), leukocyte-EVs, and endothelial-EVs levels 24-h and 7-days after IS as novel diagnostic and prognostic/predictive biomarkers in 28 acute IS and 35 control patients. Methods: Blood samples of 28 patients diagnosed with acute IS with hyper platelet reactivity were collected 24-h and 7-days after stroke and 35 age- and gender-matched individuals free of stroke with multiple risk factors for cardiovascular disease. Platelet reactivity was assessed by AA-, TRAP-, ADP-induced platelet aggregometry. PlasmaRNA was extracted; quality RNA was assessed: fluorometric assay; RT-PCR for miRNAs expression measurement and flow-cytometry for EVs determination p<0.05. Results: Patients with IS on day-1 had significantly higher platelet reactivity assessed by AA-induced platelet aggregometry compared to controls (p=0.001). Patients with normal platelet activation had significantly higher miR-186-5p expression levels compared to patients with HPR at day-1 acute-stroke (p=0.034). Seven days after acute stroke, expression levels of miR-186-5p significantly decreased in the same patients with normal platelet reactivity (p=0.036). Patients with HPR had significantly elevated platelet-EVs (CD62) concentration compared to patients with normal platelet reactivity at the day of 1 acute-stroke (p=0.012). Similarly, patients with HPR had significantly higher leukocyte-EVs (CD45) concentration compared to patients with normal platelet function at day-1 acute-stroke (p=0.002). Diagnostic values of baseline miRNAs and EVs were evaluated with receiver operating characteristic curve analysis. ROC curve showed that pooling the miR-19a-3p expressions, platelet-EVs, and leukocyte-EVs concentration yielded a higher AUC than the value of each individual biomarker as AUC was 0.893 (95% CI, 0.79–0.99). Patients with moderate stroke had significantly elevated miR-19a-3p expression levels compared with patients with minor stroke at the day of acute IS. AUC in ROC curve analysis was 0.867, (95% CI, 0.74–0.10) p=0.001. Conclusions: Our analysis showed alteration of circulating miRNAs and EVs after IS. Combination of miR-19a-3p, Let-7f, platelet-EVs and leukocyte-EVs might have a diagnostic value for acute stroke and miR-19a-3p can predict the severity of stroke in IS patients. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Science Centre - Narodowe Centrum Nauki